In vivo biocompatibility and long-term durability of nanofibrillated cellulose as a urethral bulking agent in rats and Beagle dogs - Nina M. M. Peltokallio; Stéphanie Noël; Géraldine Bolen; Satu Kuure; Eija Raussi-Lehto; Guillermo Reyes; Rubina Ajdary; Jani Kuula; Annick Hamaide; Outi M. Laitinen-Vapaavuori (PLoS ONE, 2025)
Background Cystoscopy-assisted submucosal injections of urethral bulking agents offer a safe and efficient alternative to surgery for treating urinary incontinence in both dogs and women. To address the concern of their transient therapeutic effect, a preclinical study evaluating the biocompatibility, safety, and durability of nanofibrillated cellulose as a bulking agent was designed. Plant-based nanofibrillated cellulose is considered renewable, biocompatible, and non-degradable in vivo. To the best of our knowledge, no studies of nanofibrillated cellulose injected into the urethral wall of experimental animals have been published to date. Methods After assessing the rheological behavior of nanofibrillated cellulose, a biocompatibility study with 50 rats and a durability study with two Beagle dogs were conducted. In anesthesized rats, deposits of either nanofibrillated cellulose or sodium chloride as an inert control were injected into the urethral wall via a caudal laparotomy. The rats were euthanized for histopathological assessment after 7, 30, and 90 days. In dogs, cystoscopy-assisted injections of nanofibrillated cellulose were followed with magnetic resonance imaging at 14 days and at 2, 3, 6, and 12 months. Results The rheological studies demonstrated a gel-like behavior under a wide range of shear stress. Nanofibrillated cellulose induced a moderate host tissue response according to the EN ISO 10993-6 standard, consisting primarily of macrophages, foreign body giant cells, lymphocytes, and plasma cells. No significant difference was observed in the tissue response at different time points. In dogs, the bulking agent was visible in 4/5 (80%) injection sites on magnetic resonance imaging at 12 months post-injection. No signs of migration, abscess formation or any major or long-term complications were observed. Conclusions Nanofibrillated cellulose maintains a chronic but stable and tolerable inflammatory response for up to 90 days in the urethral wall of rats. Durability in the urethral wall of dogs indicates a potential long-term effect.